Routing and Wavelength Assignement: Comparison of Simulated Annealing and Genetics Algortihm [Ruteo y Asignación de Longitud de Onda: Comparación de Algoritmos Genéticos y Templado Simulado] - Gutierrez-Osorio, A; Rivera-Mendez, L; Rivera-Mendez, L; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2014)
In this paper compares studies over routing and wavelength assignment for better some services indicators, such as blocking probability and network utilization. In modern telecommunications are gradually subjected to increased demand, which results in higher requirements in photonic transport networks. This phenomenon forces us improve routing systems, in order to better serve current demand and have capacity of attention of future demand. The comparison is made between the algorithms Genetic Algorithms and Simulated Annealing, both simulated in the optical network NSFNET using wavelength division multiplexing WDM. The results showed that heuristic algorithms are better in dynamic demand and high charge, functioning better under stress. It is concluded that genetic algorithms provide the best solution for future demand.